Sum of ranking differences to rank stationary phases used in packed column supercritical fluid chromatography - West, Caroline; Khalikova, Maria A; Lesellier, Eric; Héberger, Károly (Journal of chromatography. A, Including electrophoresis and other separation methods, 2015)
The identification of a suitable stationary phase in supercritical fluid chromatography (SFC) is a major source of difficulty for those with little experience in this technique. Several protocols have been suggested for column classification in high-performance liquid chromatography (HPLC), gas chromatography (GC), and SFC. However, none of the proposed classification schemes received general acceptance. A fair way to compare columns was proposed with the sum of ranking differences (SRD). In this project, we used the retention data obtained for 86 test compounds with varied polarity and structure, analyzed on 71 different stationary phases encompassing the full range in polarity of commercial packed columns currently available to the SFC chromatographer, with a single set of mobile phase and operating conditions (carbon dioxide-methanol mobile phase, 25°C, 150bar outlet pressure, 3ml/min). First, a reference column was selected and the 70 remaining columns were ranked based on this reference column and the retention data obtained on the 86 analytes. As these analytes previously served for the calculation of linear solvation energy relationships (LSER) on the 71 columns, SRD ranks were compared to LSER methodology. Finally, an external comparison based on the analysis of 10 other analytes (UV filters) related the observed selectivity to SRD ranking. Comparison of elution orders of the UV filters to the SRD rankings is highly supportive of the adequacy of SRD methodology to select similar and dissimilar columns.
Keywords: oxid uhličitý; superkritická fluidní chromatografie; methanol; Pressure; Carbon Dioxide; tlak; Chromatography, Supercritical Fluid; Methanol